Factor rotation with non-negativity constraints - Stephen Pudney (Centre for Microdata Methods and Practice (cemmap), 2011)
Factor rotation is widely used to interpret the estimated factor loadings from latent variable models. Rotation methods embody a priori concepts of 'complexity' of factor structures, which they seek to minimise. Surprisingly, it is rare for researchers to exploit one of the most common and powerful sources of a priori information: non-negativity of factor loadings. This paper develops a method of incorporating sign restrictions in factor rotation, exploiting a recently-developed test for multiple inequality constraints. An application to the measurement of disability demonstrates the feasibility of the method and the power of non-negativity restrictions.
Keywords: C12; C38; I10; 330; Factor rotation; Inequality constraints; Chen-Szroeter test; Disability